A pH responsive nanocomposite for combination sonodynamic‐immunotherapy with ferroptosis and calcium ion overload via SLC7A11/ACSL4/LPCAT3 pathway - Xue Bai; Jun Kang; Silong Wei; Yun Wang; Yangsui Liu; Bo Yuan; Qian Lu; Huansong Li; Jun Yan; Xi Yang; Jin Chang (Exploration)
Abstract Sonodynamic therapy offers a non‐invasive approach to induce the death of tumor cells. By harnessing ultrasound waves in tandem with sonosensitizers, this method produces reactive oxygen species (ROS) that inflict oxidative damage upon tumor cells, subsequently causing their demise. Ferroptosis is a regulatory form of cell death that differs from other forms, characterized by iron accumulation, ROS accumulation, and lipid peroxidation. In the presented research, a nanoparticle formulation, parthenolide/ICG‐CaCO3@lipid (PTL/ICG‐CaCO3@Lip), has been engineered to amplify ferroptosis in tumor cells, positioning it as a potent agent for sonodynamic cancer immunotherapy. This nanoparticle significantly augments ROS levels within tumor cells, inducing oxidative stress that leads to cell death. The therapeutic potential of PTL/ICG‐CaCO3@Lip, both in vivo and in vitro, has been convincingly demonstrated. Furthermore, RNA‐seq analysis insights revealed that PTL/ICG‐CaCO3@Lip facilitates tumor cell ferroptosis by regulating P53 to downregulate SLC7A11 protein expression, thereby inhibiting the glutamate‐cystine antiporter system Xc− and stimulating ACSL4/LPCAT3 pathways. This pioneering work uncovers an innovative strategy for combatting tumors, leveraging enhanced oxidative stress to promote cell ferroptosis, and paves the way for groundbreaking cancer immunotherapeutic interventions.